PERANCANGAN CYLINDER CATCHPOT VACUUM INFUSION SEBAGAI MEDIA PEMBUAT KOMPOSIT SERAT KARBON - Firman Yasa Utama; Mohammad Irfan; Annisa Kesy Garside; Andita Nataria F.G.; Ferly Isnomo Abdi (Universitas Negeri Surabaya, 2025)
The use of metal or steel in a variety of applications has begun to be replaced by Carbon Fiber Reinforced Polymer (CFRP). Some of the advantages of CFRP include mechanical strength almost equal to, and sometimes exceeding, that of metal materials. One innovation in the manufacture of carbon fibre composites is the vacuum infusion method. Resin is drawn into the mould under suction pressure from a vacuum pump. Excess resin is drained from the mould through a hose and collected in a container, which also serves to control the vacuum pressure in the mould before it enters the pump. Previously, the catchpot was made of square-shaped iron with permanently welded joints, resulting in unstable suction pressure. Additionally, the resin's fast curing properties made cleaning difficult, leading to blockages in the hose over time. These issues highlight the need for a vacuum infusion design that is easy to open and close, easy to control and leak-proof. In this study, a research and development (R&D) approach was taken. The design process for the Cylinder Catchpot Vacuum Infusion begins with the design, calculation, and design stages, and ends with functional testing. The design process takes into account dimensions and the motor power required to use ¼HP for a 1-liter catchpot. The component is manufactured through the manufacturing stage and undergoes functional testing, where the Cylinder Catchpot Vacuum Infusion tool detects no leaks in the circuit, ensuring stable pressure, and ensuring proper resin distribution throughout the fibers, ensuring no voids in the composite